2019
DOI: 10.3347/kjp.2019.57.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Prevalence of Cryptosporidium spp. in Breeding Kennel Dogs

Abstract: Cryptosporidium is a common intestinal protozoan that can lead to diarrhea in humans and dogs. The predominant species of infection are C. hominis and C. parvum in humans, and C. canis in dogs. However, C. canis can infect immunocompromised humans. Considering the close contact with humans, dogs have the potential to be reservoirs for human cryptosporidiosis. Breeding kennels are the major supply source of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Altogether, 94.3% (33/35) of the examined dogs positive for Cryptosporidium in our study were infected by the “dog type” C. canis . Analogous observations were made in studies examining breeding kennel dogs and sled dogs from Japan and Canada, respectively, in which C. canis was the only species found (Itoh et al 2019 ; Julien et al 2019 ). Furthermore, 48% of these samples (16/33) were successfully amplified targeting the GP60 gene.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Altogether, 94.3% (33/35) of the examined dogs positive for Cryptosporidium in our study were infected by the “dog type” C. canis . Analogous observations were made in studies examining breeding kennel dogs and sled dogs from Japan and Canada, respectively, in which C. canis was the only species found (Itoh et al 2019 ; Julien et al 2019 ). Furthermore, 48% of these samples (16/33) were successfully amplified targeting the GP60 gene.…”
Section: Discussionsupporting
confidence: 63%
“…The varying prevalence values may reflect variable living conditions (e.g. kennel, breeder or private dogs) (Giangaspero et al 2006 ; Hamnes et al 2007 ; Palmer et al 2008 ; Gil et al 2017 ; Sauda et al 2018 ; Alves et al 2018 ; Itoh et al 2019 ; Julien et al 2019 ), but different sampling strategies and laboratory methods may contribute to this striking variation. In China and Brazil, prevalence was 6.9% and 10.4%, respectively, irrespective of keeping conditions (Li et al 2019 ; Homem et al 2019 ) which is quite close to the values found for Eastern Germany in the present study which may indicate that regional differences are not of great impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is comparable to the prevalences in Poland (2.0% for G. duodenalis) 41 , India (3.0% for G. duodenalis) 42 , the United States (2.0% and 3.8% for Cryptosporidium) 43,44 , China (3.8% and 4.9% for Cryptosporidium) 10,14 , Italy (3.3% for Cryptosporidium) 9 , Australia (2.5% for Blastocystis) 29 , Brazil (2.6% for Blastocystis) 31 , and France (3.4% for Blastocystis) 20 . However, higher prevalences of 21% of Cryptosporidium from Japan, 36.5% of G. duodenalis from Spain, and 37.5% of Blastocystis from Colombia were also previously found in dogs 22,24,33 . Aside from geographical considerations, many factors can contribute to this difference in the prevalence, including a dog's age, origin, health status, and examination methods used.…”
Section: Discussionmentioning
confidence: 84%
“…2014 [ 65 ] Tohoku ≤3 mo 471 pet shop puppies 149 (31.6) Kanto 98 veterinary nursing school dogs Kinki 2–11 yr 18 (18.4) Kyushu Okinawa Miyagi Niigata Gunma Shizuoka Aichi 2 mo–11 yr 314 breeding kennel dogs 66 (21) 1 C. canis Itoh et al . 2019 [ 66 ] Osaka NS 1 raccoon dog* 1 1 C. parvum cattle genotype This study was conducted at Osaka Municipal Tennoji Zoological Gardens Matsubayashi et al . 2004, 2005 [ 99 , 101 ] Cats Tokyo metropolitan Variable 608 23 (3.8) NS One year survey from February, 1988 to February, 1989 …”
Section: Reported Animal Cases Of Cryptosporidiosis Species Diversitmentioning
confidence: 99%